INTEGRATING ROLE AND ATTRIBUTE-BASED ACCESS CONTROL WITH PREDICTIVE ANALYTICS FOR DYNAMIC ACCESS DECISIONS - Basireddy Vijaya Lakshmi,; Dr. Nagarjuna Karyemsetty, (Utilitas Mathematica, 2025)
Access control plays a vital role in information security, ensuring that only authorized individuals can access specific resources. This study introduces a hybrid access control model that merges Role-Based Access Control (RBAC) with Attribute-Based Access Control (ABAC) to improve both flexibility and scalability. RBAC streamlines management by assigning permissions according to defined roles, whereas ABAC provides detailed access control based on user attributes, resource characteristics, and environmental factors. By combining these two models, the proposed method overcomes the shortcomings of traditional RBAC systems while still allowing for effective management. The paper outlines the implementation, architecture, and assessment of the hybrid RBAC-ABAC model, showcasing its ability to strike a balance between security and usability.